"BEAUTIFUL GIRLS and antiquities": Visuella och narrativa representationer av Visby och Gotland - Johansson, Carina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
This text focuses on narrative and visual representations of Visby and Gotland in tourism mindscapes. In Visby, the Middle Ages have become "the Age" that determines the tourist’s gaze. Numerous paintings, photos and other visual images back up narratives to make Visby visible and well known in a very specific way — as a medieval theme city. This process, thus highlighting specific objects, creates views, symbols and icons, reproduced over and over again. Narratives connected with images characterize the dominant mindscape in well-known ways. In my article, I show what happens when images showing something else and unexpected suddenly appear. The ideas of blurred genres and competitive disursive fields can explain the clash between the conflicting mindscapes.